Intracranial aneurysm surgery: a case serie - Seddighi, Afsoun; Seddighi, Amir Saied; RahimiBaghdashti, Hesam; Vahidi, Mehrnush; Ashrafi, Mahsa; Yaghubi, Mohmmad Yousef (International Clinical Neuroscience Journal, 2015)
Background: Intracranial aneurysms are fatal but also curable diseases of nervous system which often present suddenly with Subarachnoid Hemorrhage (SAH). The aim of this study is to show the results of 7 years surgery performed on patients with intracranial aneurysm admitted in our center. Methods: This study is a retrospective case series that is performed by "existing data" in patient’s documents. Different factors such as age, sex, sign and symptoms, anatomical location of deficit and before-after surgery complications have been analyzed. Results: From February 2003 to June 2010, 54 cases (totally 62 aneurysms) were operated in our center. Male to female ratio was 1.28 and mean age was 50.47 years. The most common symptom was sudden severe headache. The most common sites were anterior communicating artery (40%), internal carotid artery bifurcation (35%) and middle cerebral artery (25%). Most of the patients were in grade 1 of Hunt & Hess scale. The most common mortality was due to cardiopulmonary arrest. Conclusion: Considering that mortality rate in older patients with different risk factors is so high, it seems that operating these patients on an emergency basis and intensive care for vasospasm leads to favorable outcome.